Peran Etika Profesi dalam Pembentukan Budaya Organisasi di PT. Bank Syariah Indonesia Tbk - Neni Karlena; Alfiatul Hasanah; Rimi Gusliana Mais (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the role of professional ethics in shaping organizational culture at PT Bank Syariah Indonesia Tbk and its influence on employee performance. Professional ethics function as behavioral guidelines that regulate integrity, responsibility, competence, and employees’ moral standards, thereby influencing work patterns and the values that develop within the organization. This study employs a qualitative approach using a literature review (library research) method, drawing on scholarly journals, books, and official reports relevant to professional ethics, organizational culture, and work behavior at PT Bank Syariah Indonesia Tbk. The findings indicate that the work environment, organizational culture, and Islamic work ethics play an important role in supporting the performance of Bank Syariah Indonesia employees. These findings are supported by interview and observational results, which indicate a relationship between these three aspects and improvements in employee work quality. The implications of this study emphasize that PT Bank Syariah Indonesia Tbk needs to strengthen its systems of education, supervision, and enforcement of the code of ethics in order to create a healthy, professional, and sustainable organizational culture.